PENGARUH CITRA MEREK, DESAIN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ROKOK ESSE DI BUKIT TINGGI - Maria Magdalena; Agus Satria Prama Diva (LP2M Universitas Bina Bangsa, 2023)
This study has a problem formulation, namely whether brand image affects the purchasing decision of esse cigarettes in Bukit Tinggi and whether product design affects the purchasing decision of esse cigarettes in Bukit Tinggi. This study aims to determine the effect of brand image, product design and price on purchasing decisions of esse cigarettes in Bukit Tinggi. This type of research is quantitative research. The sample consists of 96 people who use esse cigarettes by using accidental sampling. Analysis of the data used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that the brand image variable partially had a positive and significant effect on purchasing decisions for esse cigarettes in Bukit Tinggi. Meanwhile, Product Design Variables have a positive and significant positive effect on purchasing decisions for esse cigarettes in Bukit Tinggi. And the price variable has a positive and significant positive and significant effect on purchasing decisions for esse cigarettes in Bukit Tinggi